O patrimônio de Dom Viçoso: economia e sociabilidade entre camponeses da região da Serra do Brigadeiro - MG - Marisa Alice Alves (2008)
This dissertation addresses the subject of economy and sociability amongst peasants who live in the district of Dom Viçoso, situated in the municipality of Ervália, in the region of the Serra do Brigadeiro, state of Minas Gerais. Fieldwork was undertaken in the center of this district, which constitutes a patrimônio (patrimony) or terra de santo (saints land). Around a hundred families live in this area. They are agriculturists who cultivate lavouras and roças (farmings) in terrenos (little farms or peasant farms) situated in the outskirts of the patrimônio. Such agriculturists differentiate themselves in economic terms, mainly concerning access to the means of production, especially land. In spite of these economic differences, I consider all agriculturists of the patrimônio as pertaining to the category peasants. In my pursuit of a dialogue with the literature on peasants, I consider this concept as referring not only to a modality of family agriculture that presents relative economic and social autonomy, but, mainly, to a specific socio-cultural formation. Thus, I argue that the economy in a peasant context must be analyzed in reference to the social system as a whole, and that the peasant specificity is always defined in a contextual and historical way. In the studied case, the distinct categories of agriculturists compose one social universe defined by the experience shared in the patrimônio, which is socially constructed by such agriculturists as its territory and the nucleus of their sociability. Therefore, the economic differentiation in Dom Viçoso does not imply in a social stratification, because the agriculturistss economic practice are guided by a peasant moral. This moral is defined in the context of the local sociability, which is structured by the principles of kinship.